(untitled) (Academic Journal of Internal Affairs, 2021)
The COVID-19 pandemic has shocked the entire world, placing an additional burden on all people, regardless of gender, age, health condition, or social status. The pandemic also affects women’s decision to have children, pregnancy, childbirth circumstances, parental involvement, health status, and partnerships. The study addresses the challenges for women, in particular the situation of the female staff serving in the police force, who also have to cope with the increased workload resulting from the epidemic.